Ultrasound-Assisted Extraction of Protein from IMoringa oleifera/I Seeds and Its Impact on Techno-Functional Properties - Fatima, Khushar; Imran, Muhammad; Ahmad, Muhammad Haseeb; Khan, Muhammad Kamran; Khalid, Waseem; AL-Farga, Ammar; Alansari, Wafa S; Shamlan, Ghalia; Eskandrani, Areej A (Molecules (Basel, Switzerland), 2023)
Plant proteins can be an important alternative to animal proteins subject to minor modification to address sustainability issues. The impact of ultrasound application on the yield, techno-functional properties, and molecular characteristics of protein extracted from Moringa oleifera seeds was studied. For this purpose, a central composite design (CCD) was applied to optimize ultrasound-assisted extraction (UAE) parameters such as amplitude (25–75%), solute-to-solvent ratio (1:10–1:30), and pH (9–13) for obtaining the maximum protein yield. At the optimized conditions of 75% amplitude, 1:20 solute-to-solvent ratio, and 11 pH, a protein yield of 39.12% was obtained in the UAE process. Moreover, the best sonication time at optimized conditions was 20 min, which resulted in about 150% more extraction yield in comparison to conventional extraction (CE). The techno-functional properties, for instance, solubility, water (WHC)- and oil-holding capacity (OHC), and emulsifying and foaming properties of the protein obtained from UAE and CE were also compared. The functional properties revealed high solubility, good WHC and OHC, and improved emulsifying properties for protein obtained from UAE. Although protein from UAE provided higher foam formation, foaming stability was significantly lower.